Optical absorption measurements and optoelectronic DFT calculations for ethanol solvated quercetin and anhydrous/hydrated quercetin crystals (2022)
UV–vis optical absorption measurements of the ethanol solvated quercetin molecule and the dihydrate triclinic quercetin crystal were performed, as well as the electronic structure of the ethanol solvated quercetin molecule and the properties of anhydrous and mono(di)hydrated quercetin crystals employing Density Functional Theory (DFT) calculations with a dispersion correction scheme. Unit cell geometry optimization of the anhydrous crystal has elucidated the structure of the anhydrous quercetin crystal (space group P21/a, monoclinic). Anhydrous quercetin exhibits a direct bandgap of 2.17 ​eV with large valence band dispersion, suggesting a semiconductor behavior for hole transport. Monohydrate quercetin has an indirect gap of 1.84 ​eV, while the solid dihydrate form has a Kohn-Sham indirect electronic bandgap of 2.00 ​eV, smaller than the experimental optical absorption bandgap of 2.40 ​eV. Applying the Δ-sol gap correction scheme, the bandgaps increase by about 1 ​eV. There is a significant optical anisotropy for all quercetin systems in the solid state, especially for the anhydrous form. © 2022 Elsevier Inc.